Analysis Of The Character Of Karin In The Novel Maharku Surah Ar-Rahman By Ahliya Mujahidin: Gestalt Approach (Kurt Kofkka) - Dewi Fitriya; Safina Amalia Oktaviana Anwar (Demagogi: Journal of Social Sciences, Economics and Education, 2024)
The novel "Maharku Surah Ar-Rahman" by Ahliya Mujahidin depicts the journey of its main character, Karin, through the lens of a life filled with meaning. In analyzing Karin's character, the Gestalt approach, developed by Kurt Kofkka, can provide deep insight into the way Karin organizes and integrates her life experiences. The Gestalt approach emphasizes observation of the whole, where parts of an individual's experience form a larger whole. In the context of Karin's character, this reflects how every event in her life is interconnected and contributes to her overall understanding. Karin as the main character in this novel has complex emotional layers. The Gestalt approach can help us see how important events in his life, such as loss and happiness, form a complete picture of his personality. For example, how feelings of loss in the past affect the way Karin interacts with the people around her and shapes her thinking patterns. In Gestalt, there is the concept of "organization" which shows how individuals structure their experiences into a meaningful pattern. Karin, as a character, may face internal conflicts that need to be organized to achieve unity in her development. Gestalt analysis can help identify key points in the story that help shape this character organization. Additionally, the Gestalt approach highlights the importance of context in understanding individuals. Karin is not only analyzed as a separate entity, but also in relation to her environment, social relationships, and cultural context. This opens up the opportunity to understand how external factors play a role in his character development. By applying the Gestalt Approach in analyzing Karin's character, we can find continuity and integration between various aspects of her life. This provides a richer understanding of the complexity of the character in the context of the novel "Maharku Surah Ar-Rahman" by Ahliya Mujahidin, and how his life experiences form the overall pattern that makes him a strong and multidimensional character.